Improving Learning Discipline through Self-Management Techniques for Students at SMA Negeri 1 Kedamean - Natasya, Anggi; Wicaksono, Awang Setiawan (Universitas Muhammadiyah Gresik, 2024)
Discipline is problem important in the teaching and learning process in school. Effort increase students discipline in building atmosphere that can be motivate students in change Act in demand or change leading behavior to things positive . With discipline student willing to submit And follow regulation certain And stay away prohibition certain . To overcome problem discipline Study need given the behavioral approach is wrong the other is by technique self-management . Technique This is to guide students in effort improve discipline Study And in a way aware desire to change his behavior Alone . Hopefully with technique change behavior can replace behavior correct student use to improve discipline Study. Technique Self-Management This done in stages assessment , stage intervention , follow up or follow carry on . On research this researcher using 9 students from 3 classes with scores low discipline. Researcher implement this program for 6 meetings . Based on results research conducted to 9 is obtained results enhancement discipline studied by students at SMA Negeri 1 Kedamean .